THE SCHEME OF SIMULATION CASES FOR MATHEMATICAL MODELING OF HELICOPTER DYNAMICS WITH THE CARGO ON THE EXTERNAL SLING AT TAKEOFF AND LANDING PHASES - V. V. Efimov; A. Elsaidabdo (Научный вестник МГТУ ГА, 2017)
When a helicopter performs an air operation and aerial work using external sling there may occur special situations, as the result of unfavourable conditions impact. The most difficult and dangerous stages of flight are the takeoff and landing.To study an aircraft flight dynamics in extreme flight conditions, including a helicopter with cargo on external sling, the most effective is to use the theoretical methods, mathematical modeling in particular, which is relatively cheap, able to model the abnormal situation including disasters, and able to set the necessary environ-mental effect.During the theoretical studies it is impractical and impossible to simulate all the abnormal situations that may occur at the given phases of flight. Therefore, at the initial stage of the research it is necessary to deal with making up a list of the most typical abnormal situations - the scheme of simulation cases. This issue is the subject of this article.The article describes the typical errors of piloting a helicopter with cargo on external sling at takeoff and landing, as well as the most dangerous equipment failures and noncalculated operating conditions, based on the analysis of which the scheme of simulation cases has been made. After modeling in accordance with the scheme of simulation cases, it will be possible to determine the effect of the cargo parameters, flight parameters, the impact of unfavourable factors on the dynamics of the system "helicopter - cargo on external sling" at takeoff and landing, which theefore will determine the boundaries of the system safe operation on these phases of flight, and to formulate recommendations for the crew to prevent abnomal situations or to get out of them.For further research it is expected to use the earlier developed HeliCargo software application, which allows to simulate the dynamics of helicopter with cargo on external sling.